Direito à cidade: relações e vivências na Areninha Genibaú da cidade de Fortaleza, Ceará - Nunes, Juliana da Silva (2023)
This paper is the result of a field research that aims to analyze the relationships that are established in the Areninha Genibaú, located on the outskirts of the city of Fortaleza, Ceará, from the perspective of the right to the city. It examines, thus, the sociabilities that are made possible from a space in the city and that is related to the city in general, both locally and in its global context. For this, we carried out field research and dialogues with the users of the equipment, besides making use of manuals and documents about the sports and leisure policy, as well as images taken from Google. As a result, it is observed that the proposal of the Sport and Leisure Policy carried out through the Areninhas expands the possibility of access to leisure for the population, however, it lacks articulation with other public policies, in order to make the right to the city more democratic. It is observed that the gender issue permeates the practices carried out in the equipment, having as a more expressive public the masculinities, among the practices it stands out the soccer and carimba games, the battle arena and the informal street food trade. It is considered, therefore, that while access to leisure is attributed only to access to equipment, without considering the reality expressed in the urban space, it will take place in a fragmented way, not reaching the population contingent.